2007
DOI: 10.1002/mrd.20672
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of rabbits to superovulation treatment by a single injection of follicle‐stimulating hormone with aluminum hydroxide gel

Abstract: Aluminum hydroxide gel (Al-gel), which is used as an adjuvant, can absorb macromolecules. We investigated the applicability of Al-gel to the sustained release of follicle-stimulating hormone (FSH) as a simplified method of superovulation (SOV) in rabbits. The responsiveness of rabbits to SOV by a single injection of FSH dissolved in Al-gel suspension (3.2 mg Al/ml) and in 10% (w/v) polyvinylpyrrolidone (PVP), and by multiple injections of FSH in saline was examined. The numbers of total and fertilized eggs rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…On the basis of the rapid clearance of FSH (w5 hours) [39], regardless of the dose administered [55], an alternative could be to modify hormone absorption. Modifications examined have included changing the route administration (subcutaneous injection, [55][56][57]) or mixing the pFSH with polymers, such as polyvinylpyrrolidone [58], aluminum hydroxide gel [59] or HA [42] to reduce the rate of absorption. Tríbulo et al [42] reported satisfactory superovulatory results after treating Table 1 Summary of cumulus-oocyte complex yield and in vitro embryo production (mean AE standard error or percentage) in nonlactating Holstein cows that were not treated (control), treated with 200 mg of porcine FSH (pFSH; F200) in twice-daily injections or 200 or 300 mg of pFSH as a single injection in 0.5% hyaluronan (F200HA and F300HA).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the rapid clearance of FSH (w5 hours) [39], regardless of the dose administered [55], an alternative could be to modify hormone absorption. Modifications examined have included changing the route administration (subcutaneous injection, [55][56][57]) or mixing the pFSH with polymers, such as polyvinylpyrrolidone [58], aluminum hydroxide gel [59] or HA [42] to reduce the rate of absorption. Tríbulo et al [42] reported satisfactory superovulatory results after treating Table 1 Summary of cumulus-oocyte complex yield and in vitro embryo production (mean AE standard error or percentage) in nonlactating Holstein cows that were not treated (control), treated with 200 mg of porcine FSH (pFSH; F200) in twice-daily injections or 200 or 300 mg of pFSH as a single injection in 0.5% hyaluronan (F200HA and F300HA).…”
Section: Discussionmentioning
confidence: 99%
“…116,117 Sustained-release formulations of FSH are also in development that could result in a decreased number of gonadotropin doses. 118 In contrast to the LH receptor, both low molecular weight agonists and antagonists have been identified for the FSH receptor. FSH receptor antagonists may be used as non-hormonal contraceptives.…”
Section: F S H R E C E P T O R L I G a N D Smentioning
confidence: 99%
“…A single administration of FSH in PVP has been used to induce SOV in rabbits [56, 57]. We previously used AH-gel as an adsorbent for FSH for the SOV in rabbits [58]. We found that the numbers of total and fertilized eggs recovered from rabbits treated with FSH in AH-gel were similar to multiple FSH injections and were significantly greater than the numbers obtained from a single injection of FSH with PVP.…”
Section: Application Of a Single Administration Of Fsh In Ah-gel To Omentioning
confidence: 99%